Financial Uncertainty in Earnings Per Share and Stock Prices: A Monte Carlo Simulation Study of US Business Services Multinationals - Chatterjee, Suranjana (Journal of Global Economy, Business and Finance, 2025)
This study examines the financial uncertainties in EPS income and share price predictions for 30 U.S. multinational corporations and MNCs in the Business Services Global Industry. Using Monte Carlo simulation with 20,000 iterations and a 99% confidence level, the results suggest that market consensus on EPS and share prices may be overly optimistic. The findings highlight the potential discrepancies between predicted revenue and actual market conditions, emphasizing the need for cautious forecasting in future financial analyses.